Intraocular Water Movement Visualization Using 1H‐MRI With Eye Drops of O‐17‐Labeled Saline: First‐in‐Human Study. Issue 3 (15th July 2022) - Tomiyasu, Moyoko; Sahara, Yasuka; Mitsui, Etsuko; Tsuchiya, Hiroki; Maeda, Takamasa; Tomoyori, Nobuhiro; Kawashima, Makoto; Nogawa, Toshifumi; Kishimoto, Riwa; Takado, Yuhei; Higashi, Tatsuya; Mizota, Atsushi; et al.
Abstract : Background: Visualization of aqueous humor flow in MR contrast images using gadolinium is challenging because of the delayed contrast effects associated with the blood‐retinal and blood‐aqueous humor barriers. However, oxygen‐17 water (H2 17 O) might be used as an ocular contrast agent. Purpose: To observe the distribution of H2 17 O in the human eye, and its flow in and out of the anterior chamber, using dynamic T2‐weighted MRI. Study Type: Prospective. Population: Six ophthalmologically normal volunteers (20–37 years, six females). Field Strength/Sequence: A 3 T/dynamic T2‐weighted MRI. Assessment: H2 17 O eye drops were administered to the right eye. Time‐series images were created by subtracting the image before the eye drops from each of the images obtained after the eye drops. The normalized signal intensity of the right anterior chamber (nAC) was obtained by dividing the signal intensity of the right anterior chamber region by that of the left. The inflow and outflow constants of H2 17 O and H2 17 O concentration were calculated from the nAC. Statistical Tests: A paired t ‐test was used to compare the flow‐related values and temporal changes in signal intensity. P ‐values < 0.05 were considered statistically significant. Results: Significantly decreased signal intensity was observed in the right anterior chamber but not the right vitreous body ( P = 0.39). The nAC signal intensity decreased significantly and then recovered. The inflow and outflow constants were 0.36–0.94 min −1 and 0.023–0.13 min −1, respectively. The maximum H2 17 O concentration was 0.078%–0.24%. Data Conclusion: H2 17 O were distributed in the anterior chamber. The H2 17 O inflow into the anterior chamber was significantly faster than that of the outflow. Level of Evidence: 2 Technical Efficacy Stage: 2